2019
DOI: 10.1002/ppsc.201900133
|View full text |Cite
|
Sign up to set email alerts
|

Tuning a Bisphenol A Lateral Flow Assay Using Multiple Gold Nanosystems

Abstract: Advanced bisphenol A (BPA) lateral flow assays (LFAs) that use multiple nanosystems are reported. The assays use three nanosystems: gold nanostars, gold nanocubes, and gold nanorods, which are rarely applied in LFAs, compared with general gold nanoparticles that are referred to as gold nanospheres in this paper. These various nanosystems are bound to anti‐BPA antibodies and applied in LFAs to develop advanced BPA LFAs; the developed LFAs show differing BPA detection performance, as well as different visible co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
(101 reference statements)
0
2
0
Order By: Relevance
“…Besides the composition of the label, the morphology and the size of the nanoparticles also play important roles in the sensitivity of LFAs. , For example, increasing the surface area of a nanoparticle allows it to load more bioreceptors (e.g., antibodies, proteins, or aptamers), or the presence of spiked structures can provide different optical properties due to surface-enhanced plasmons. In this context, several research groups have demonstrated how the use of non-spherical nanoparticles with strong plasmonic behaviors (e.g., nanorods, nanocubes, and nanostars) generally produces an improvement in the LFA sensitivity when compared to the use of classical quasi-spherical AuNPs. Looking in particular at mono- and bimetallic non-spherical nanoparticles, we found studies reporting up to 5-fold and 10-fold improvements in the sensitivity of LFAs when using gold and platinum nanoflowers, respectively. Uniquely of bimetallic nanoparticles, they have ability to display both plasmonic and catalytic behavior (e.g., Au-based alloy nanoparticles). , This feature has been recently harnessed by two works, where AuPt core–shell and AuPt nanoflowers have been described as dual labels for LFAs, increasing dramatically the sensitivity of the assay up to 2 orders of magnitude. , Thus, non-spherical and hierarchical nanoparticles appear as promising labels to enhance the analytical properties of LFAs.…”
Section: Introductionmentioning
confidence: 88%
“…Besides the composition of the label, the morphology and the size of the nanoparticles also play important roles in the sensitivity of LFAs. , For example, increasing the surface area of a nanoparticle allows it to load more bioreceptors (e.g., antibodies, proteins, or aptamers), or the presence of spiked structures can provide different optical properties due to surface-enhanced plasmons. In this context, several research groups have demonstrated how the use of non-spherical nanoparticles with strong plasmonic behaviors (e.g., nanorods, nanocubes, and nanostars) generally produces an improvement in the LFA sensitivity when compared to the use of classical quasi-spherical AuNPs. Looking in particular at mono- and bimetallic non-spherical nanoparticles, we found studies reporting up to 5-fold and 10-fold improvements in the sensitivity of LFAs when using gold and platinum nanoflowers, respectively. Uniquely of bimetallic nanoparticles, they have ability to display both plasmonic and catalytic behavior (e.g., Au-based alloy nanoparticles). , This feature has been recently harnessed by two works, where AuPt core–shell and AuPt nanoflowers have been described as dual labels for LFAs, increasing dramatically the sensitivity of the assay up to 2 orders of magnitude. , Thus, non-spherical and hierarchical nanoparticles appear as promising labels to enhance the analytical properties of LFAs.…”
Section: Introductionmentioning
confidence: 88%
“…The sensitivity of SERS nanotags is determined by plasmonic enhancement of the nanoparticle and the Raman scattering cross-section of the reporter molecule/ dye. [1,16] Therefore, to improve the sensitivity of SERS-LFA, there have been efforts to form hot spots by using advanced nanoparticles such as nanocubes, [17] nanostars, [18,19] core-shell particles, [20,21] hollow alloy particles, [22] or particle assemblies. [23] In addition to the type of nanoparticle, the SERS intensity also critically depends on the type of Raman reporter/dye.…”
Section: Introductionmentioning
confidence: 99%